2012
DOI: 10.5142/jgr.2012.36.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Free Radical-scavenging Activity Changes of Ginsenoside Re by Maillard Reaction and Its Possible Use as a Renoprotective Agent

Abstract: Reactive oxygen species play critical role in kidney damage. Free radical-scavenging activities of Panax ginseng are known to be increased by heat-processing. The structural change of ginsenoside and the generation of Maillard reaction products (MRPs) are closely related to the increased free radical-scavenging activities. In the present study, we have demonstrated the Maillard reaction model experiment using ginsenoside Re and glycine mixture to identify the renoprotective effect of MRPs from ginseng or ginse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The first type has been subjected to steaming and drying, known as red ginseng (RG), and the second type, which has been subjected to air drying only, is known as white ginseng (WG). In this regard, Yamabe et al [10] reported that the free radical scavenging activities in ginseng are increased by heating processes. Clinically, it is well known that RG offers more potent effects than WG, and therefore, is used more often in treating heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The first type has been subjected to steaming and drying, known as red ginseng (RG), and the second type, which has been subjected to air drying only, is known as white ginseng (WG). In this regard, Yamabe et al [10] reported that the free radical scavenging activities in ginseng are increased by heating processes. Clinically, it is well known that RG offers more potent effects than WG, and therefore, is used more often in treating heart diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Similar intercellular antioxidant activity was also reported for sugar–amino acid MRPs in AAPH‐induced RAW264.7 cells . Studies from ginsenoside Re and glycine MR system revealed that the structural changes of ginsenoside during the reaction were closely related to the increased free radical‐scavenging activities . Therefore, the structure of the Pz‐Lys MRPs fractions was characterised by FTIR.…”
Section: Resultsmentioning
confidence: 99%
“…Yamabe et al reported that the free radical scavenging activities in ginseng are increased by heating processes. 15 Clinically, it is well known that RG offers more potent effects than WG, therefore, RG is used more often for treating cardiovascular diseases. Interestingly, RG has been shown to comprise structural transformations in the active properties, particularly in ginsenosides when steamed and dried from P. ginseng.…”
Section: Introduction Mmentioning
confidence: 99%